INTERNALISASI NILAI ETNOPEDAGOGIK PADA PERMAINAN TRADISIONAL ENGKLEK SEBAGAI MEDIA PENGUATAN KARAKTER SISWA SEKOLAH DASAR - Rian Sri Nugroho; Rizal Taufik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary education plays a fundamental role in forming student character dispositions, not merely transferring cognitive knowledge. However, current educational practices are often trapped in rigid academic routines, neglecting affective aspects and local cultural values. This study aims to describe the internalization process of ethnopedagogical values contained in the traditional Engklek game and its potential as a medium for strengthening student character. This research employs a descriptive qualitative method with a value analysis approach. Data collection was conducted through participant observation and literature study to identify pedagogical values embedded in the game's rules and activities. The results indicate that the structure of the Engklek game facilitates the internalization of three main character traits: (1) Integrity, built through compliance with line rules without external authority supervision; (2) Perseverance, formed through efforts to maintain physical and mental balance and persistence after failure; and (3) Social Discipline, fostered through compliance with turn-taking culture. This study concludes that Engklek serves not only as a recreational activity but as an effective pedagogical medium for instilling character education rooted in local wisdom